Effects of Productive Zakat Management During The Pandemic for Small Business Actors in The City of Salatiga, Central Java - Roqib, Moh.; Fathan Budiman,; Faozan, Akhmad; Abdul Khalim, Mustapahayuddin (Advances in Humanities and Contemporary Studies, 2024)
The aim of the research is to explain the management of productive zakat carried out by the Salatiga City National Amil Zakat Agency (BAZNAS) during a pandemic. During this pandemic, of course, many problems have arisen. This study used descriptive qualitative method. The main problem is the management of productive zakat which has not been optimally carried out and managed professionally according to its purpose. The results of the study show that the management of productive zakat during the pandemic can be felt by small businesses in Salatiga City and is in accordance with the mandate of the law. Number 23 of 2011 concerning the management of zakat. But in the management of productive zakat, especially Human Resources (HR) still needs to be improved. Mustahiq assistance still needs to be intensified, as well as socialization regarding productive zakat needs to be carried out even more massively. As a result, this has an impact on the sub-optimal management of productive zakat in a good and professional manner.